Recipient sepsis caused by Lactococcus garvieae contamination of platelets from a donor with colon cancer. Issue 2 (12th December 2018) - Nakamura, Shuichi; Nakai, Kenji; Sakata, Momoko; Nagaoka, Yoshio; Yoshida, Kozue; Katsumata, Uichiro; Chiba, Toshimi; Matsubayashi, Keiji
Abstract : Lactococcus garvieae is a well‐known fish pathogen that has low virulence in humans and is rarely isolated from the blood cultures of endocarditis patients. We describe herein the first reported case of transfusion‐transmitted L. garvieae sepsis caused by a contaminated platelet concentrate from a donor who consumed raw octopus before blood donation. Retrospective examination of the laboratory results of the index donor revealed that his haemoglobin levels had been steadily decreasing, which led to the detection of a latent colon cancer. The donors with colon lesions involving a latent cancer may relate an asymptomatic bacteremia.